2008
DOI: 10.1002/anie.200703883
|View full text |Cite
|
Sign up to set email alerts
|

Heterocyclic Carbenes: Synthesis and Coordination Chemistry

Abstract: The chemistry of heterocyclic carbenes has experienced a rapid development over the last years. In addition to the imidazolin-2-ylidenes, a large number of cyclic diaminocarbenes with different ring sizes have been described. Aside from diaminocarbenes, P-heterocyclic carbenes, and derivatives with only one, or even no heteroatom within the carbene ring are known. New methods for the synthesis of complexes with N-heterocyclic carbene ligands such as the oxidative addition or the metal atom template controlled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
891
0
10

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 2,662 publications
(917 citation statements)
references
References 698 publications
(524 reference statements)
16
891
0
10
Order By: Relevance
“…[1][2][3][4][5] However, despite the vast number of possible Nheterocycles that could be classified as carbenes, the activity in NHC chemistry has concentrated by and large on 2-imidazolylidenes -often called 'Arduengo'-carbenes. [1][2][3][4][5] Only recently it has been shown that an abnormal binding mode via the C4 (or C5) position of imidazolylidenes yields extraordinary electron rich metal centers. [6][7][8][9][10][11][12][13][14][15][16][17] These discoveries led to a considerably increased interest in "non-classical" NHCs, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] However, despite the vast number of possible Nheterocycles that could be classified as carbenes, the activity in NHC chemistry has concentrated by and large on 2-imidazolylidenes -often called 'Arduengo'-carbenes. [1][2][3][4][5] Only recently it has been shown that an abnormal binding mode via the C4 (or C5) position of imidazolylidenes yields extraordinary electron rich metal centers. [6][7][8][9][10][11][12][13][14][15][16][17] These discoveries led to a considerably increased interest in "non-classical" NHCs, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…12 In the latter, the heterocycle is bound to a hydrogen, representing the extreme case of a C-E single bond of a triazolium adduct, whereas 2a displays the C=E double bond limit of a triazolylidene fragment. Comparison of these two extremes 65 reveals that the exocyclic double bond induces an elongation of both adjacent heterocyclic bonds C5-N1 and C5-C4. † This diagnostic structural feature allows free and metal-bound triazolylidenes to be classified.…”
mentioning
confidence: 99%
“…Methods for synthesis of NHC-metal complexes have been reviewed [23,24]. Briefly, the most common methods for synthesizing NHC-metal complexes fall into the following three classes.…”
Section: Methodsmentioning
confidence: 99%